Characterization of wami tilapia (Oreochromis urolepis hornorum) skin gelatin: microbiological, rheological and structural properties. (July 2014) - da Trindade Alfaro, Alexandre; Fonseca, Gustavo Graciano; Balbinot, Evellin; Prentice, Carlos
Gelatin was extracted from the skin of tilapia ( Oreochromis urolepis hornorum ) and its microbiological, rheological and structural properties were characterized. The tilapia skin gelatin presented typical molecular weight distribution of type I collagen with contents of imino acids (proline + hydroxyproline) of 21.67%. Gel strength and viscosity values were 221 ± 5.68 g and 5.98 ± 0.34 cP, respectively, with the maturation time of 18 ± 1 h, and both parameters increased with the maturation time. Melting and gelling points of 25 ℃ and 21 ℃, respectively, were obtained for tilapia skin gelatin. The gelatin presented microbiological standards in accordance with the Brazilian Legislation.